A Case Study of Nitrogen Saturation in Western U.S. Forests. (2001) - Fenn Fenn, Mark E. Mark E.; Poth Poth, Mark A. Mark A.
Abstract : Virtually complete nitrification of the available ammonium in soil and nitrification activity in the forest floor are important factors predisposing forests in the San Bernardino Mountains of southern California to nitrogen (N) saturation. As a result, inorganic N in the soil solution is dominated by nitrate. High nitrification rates also generate elevated nitric oxide (NO) emissions from soil. High-base cation saturation of these soils means that soil calcium depletion or effects associated with soil acidification are not an immediate risk for forest health as has been postulated for mesic forests in the eastern U.S. Physiological disturbance (e.g., altered carbon [C] cycling, reduced fine root biomass, premature needle abscission) of ozone-sensitive ponderosa pine trees exposed to high N deposition and high ozone levels appear to be the greater threat to forest sustainability. However, N deposition appears to offset the aboveground growth depression effects of ozone exposure. High nitrification activity reported for many western ecosystems suggests that with chronic N inputs these systems are prone to N saturation and hydrologic and gaseous losses of N. High runoff during the winter wet season in California forests under a Mediterranean climate may further predispose these watersheds to high nitrate leachate losses. After 4 years of N fertilization at a severely N saturated site in the San Bernardino Mountains, bole growth unexpectedly increased. Reduced C allocation below- ground at this site, presumably in response to ozone or N or both pollutants, may enhance the bole growth response to added N.